2007
DOI: 10.1108/09615530710752991
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the turbulent flow in plane diffusers

Abstract: PurposeTo provide an analysis of turbulent flow in plane diffusers for graduate and postgraduate students (researchers) which can help them to understand turbulent flows and turbulence modelling.Design/methodology/approachSteady, incompressible, turbulent flow in two‐dimensional plane diffusers, where Reynolds averaged Navier‐Stokes (RANS) equations were simplified using the theory of turbulent boundary layers in integral form adjusted for the internal flow. To close the RANS equations, the mixing length model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Sudden or gradual contraction or expansion pipes and bends with various curved edges are the most widely used geometries in industrial applications. It was shown that such hydraulic accidents strongly influence the flow arrangement inside production lines (Rizk et al, 1996;Vujičić and Crnojević, 2003). Due to the link between bacterial removal and the flow arrangement inside pipes, several studies were carried out in order to explain the residual contamination level upstream and downstream of these geometries after a CIP procedure (Jensen et al, 2005;Lelièvre et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Sudden or gradual contraction or expansion pipes and bends with various curved edges are the most widely used geometries in industrial applications. It was shown that such hydraulic accidents strongly influence the flow arrangement inside production lines (Rizk et al, 1996;Vujičić and Crnojević, 2003). Due to the link between bacterial removal and the flow arrangement inside pipes, several studies were carried out in order to explain the residual contamination level upstream and downstream of these geometries after a CIP procedure (Jensen et al, 2005;Lelièvre et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, low values of local wall shear stress were observed (0.018 Pa for P 27 and 0.056 Pa for P 8 ) in comparison to the theoretical fully‐developed flow value for a pipe diameter of 2.30 × 10 −2 m (0.19 Pa), but the fluctuation shear rates were high enough, at both lower and higher sections (40% for P 8 , between 30 and 78% for probes P 26 , P 27 and P 28 ), to significantly contribute to the removal of spores after adhesion. The expansion angle close to 35.9° is high enough to induce streamlines separation from the wall, and, thus, recirculation zone theoretically characterized by mean wall friction forces close to zero and high‐fluctuation rate 17. This zone extends beyond the expansion, which explains the moderate contamination level (yellow zone) recorded at both top and bottom behind the expansion (zone 7).…”
Section: Methodsmentioning
confidence: 94%
“…According to Vujičić and Crnojević,17 the position of the separation point of the boundary layer near the wall depends on the angle of the diffuser and on the Reynolds number. The increase of the flow section due to the high‐opening angle of the expansion (35.9°), in addition to the highest Reynolds number tested (60,000 for 2.30 × 10 −2 m pipe dia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies such as the flow in planar symmetrical diffusers and predicting the formation of symmetric [11] or asymmetric [12] separated flow regions depending on the divergence angle and Reynolds number has been applied using the Reynolds Averaged Navier-Stokes (RANS) approach. Gerolymos et al [13] adopted Reynolds stress model to analyse the flow field structure of a dual S-duct.…”
Section: Introductionmentioning
confidence: 99%